A new synonymy of Graptocleptes bicolor (Burmeister), with taxonomical notes (Hemiptera: Heteroptera: Reduviidae: Harpactorinae: Harpactorini) - Gil-Santana, Hélcio R.; Davranoglou, Leonidas-Romanos; Neves, Juliana A. (Zootaxa, 2013)
Hiranetis coleopteroides (Walker, 1873) is here found to be conspecific with Graptocleptes bicolor (Burmeister, 1838). Graptocleptes bicolor is redescribed and the male genitalia characters are illustrated for the first time. Intraspecific morphological, color and male genitalia variability are discussed. Furthermore, the species is recorded from Paraguay for the first time.